Sport-related concussion in adolescents - Patel, D. R.; Reddy, V. (Pediatric Clinics of North America, 2010)
Sport-related concussion is a common problem encountered by pediatricians and other primary care physicians. Assessment of concussion is based on clinical evaluation. The Zurich consensus statement provides a basic framework to guide concussion management decisions and recommends an individualized approach and the exercising of clinical judgment in return-to-play decisions. This article reviews practice aspects of concussion for the adolescent athletes who present in the primary care office or clinic setting.